Everyday capabilities were a path to resilience during COVID-19: a case study of five countries. Issue 2 (12th October 2022) - Neill, Rachel; Neel, Abigail H; Cardona, Carolina; Bishai, David; Gupta, Shivam; Mohan, Diwakar; Jain, Nishant; Basu, Sharmishtha; Closser, Svea
Abstract: COVID-19 demanded urgent responses by all countries, with wide variations in the scope and sustainability of those responses. Scholarship on resilience has increasingly emphasized relational considerations such as norms and power and how they influence health systems' responses to evolving challenges. In this study, we explored what influenced countries' national pandemic responses over time considering a country's capacity to test for COVID-19. To identify countries for inclusion, we used daily reports of COVID-19 cases and testing from 184 countries between 21st January 2020 and 31st December 2020. Countries reporting test data consistently and for at least 105 days were included, yielding a sample of 52 countries. We then sampled five countries representing different geographies, income levels and governance structures (Belgium, Ethiopia, India, Israel and Peru) and conducted semi-structured key informant interviews with stakeholders working in, or deeply familiar with, national responses. Across these five countries, we found that existing health systems capacities and political leadership determined how responses unfolded, while emergency plans or pandemic preparedness documents were not fit-for-purpose. While all five countries were successful at reducing COVID-19 infections at a specific moment in the pandemic, political economy factors complicated the ability to sustain responses, with all countries experiencing larger waves of the virus in 2021 or 2022. Our findings emphasize the continued importance of foundational public health and health systems capacities, bolstered by clear leadership and multisectoral coordination functions. Even in settings with high-level political leadership and a strong multisectoral response, informants wished that they—and their country's health system—were more prepared to address the pandemic and maintain an effective response over time. Our findings challenge emergency preparedness as the dominant frame in pandemic preparedness and call for a continued emphasis on health systems strengthening to respond to future health shocks and a pandemic moving to endemic status.